Impact of police effectiveness on public trust and public cooperation with the Somalia police service: exploring the mediating role of citizen satisfaction - Ahmed-Nor Mohamed Abdi; Mohamed Bile Hashi (Cogent Social Sciences)
Extensive research has been conducted in Western countries on the impact of police effectiveness and how it influences citizens’ perceptions and attitudes toward police institutions. However, knowledge regarding these issues in post-conflict countries, such as Somalia is still unknown and needs exploration. Therefore, grounded on performance and social learning theories, this study aimed to examine how perceived police effectiveness promotes public trust in police and public cooperation with the police via the underlying mechanism of citizen satisfaction in Mogadishu, Somalia. A quantitative cross-sectional survey was used to collect data from 572 residents of various administrative units in Mogadishu, Somalia. The data were analyzed using partial least squares structural equation modeling (PLS-SEM) with SmartPLS 4.0.9.5 to test the measurement and structural models. The results uncovered a direct and indirect positive and significant impact of perceived police effectiveness on both public trust in the police and public cooperation with the police via the underlying mechanism of citizen satisfaction with the police. This study provides police agencies and policymakers with actionable recommendations. Furthermore, this study has theoretical and practical implications and offers insights for improving public perceptions of police institutions.